Analysis of 622 paediatric hospitalisations due to arterial ischaemic stroke in Poland – National Health Fund registry-based study from 2011 to 2020 - Beata Sarecka-Hujar; Michał Maluchnik; Jarosław Bartosiński; Karol Tarkowski; Agnieszka Chłoń-Domińczak; Ilona Kopyta; Dorota Raczkiewicz (Archives of Medical Science, 2022)
Introduction The present study aimed to evaluate the prevalence of arterial ischaemic stroke (AIS) in Polish children, as well as to analyse the parameters related to AIS hospitalisation, including age, gender, region, month and season of the year at admission, duration, and costs, based on data from National Health Fund (NHF) registry in 2011–2020.